Effect of PD-1:PD-L1 in Invariant Natural Killer T-Cell Emigration and Chemotaxis Following Sepsis. Issue 5 (May 2016) - Young, John S.; Heffernan, Daithi S.; Chung, Chun-Shiang; Kettenmann, Maude L.; Young, Whitney A.; Guillen, Valeria Sanabria; Cioffi, William G.; Ayala, Alfred
Abstract : ABSTRACT: Invariant natural killer T-cells (iNKT) are a subset of T-cells that play a regulatory role in sepsis. Following cecal ligation and puncture (CLP), iNKT cells emigrate from the liver and into the circulation and peritoneum in a manner dependent upon coinhibitory molecule Programmed Cell Death Receptor 1 (PD-1). We hypothesized that the effect of PD-1 on iNKT-cell emigration was dependent upon the direct PD-1:PD-L1 interaction, and that PD-1 and PD-L1 would play a role in chemotaxis and chemokine receptor expression. Adoptive transfer of Vybrant-labeled wild-type (WT) cells showed the donor iNKT cells migrated from the liver to the peritoneum following CLP, but PD-L1 deficient donor iNKT cells did not. In a chemotaxis assay, WT-iNKT cells chemotaxed to CXCL12, but PD-1 and PD-L1 deficient iNKT cells did not. Using flow cytometry to evaluate chemokine receptor expression, peritoneal iNKT expression of CXCR4 increased following CLP in the WT, PD-1, and PD-L1 deficient animals, and CXCR6 increased in the WT and PD-1 deficient animals. In conclusion here we document that the hepatic emigration of iNKT cells following CLP to the peritoneum appears dependent upon the direct PD-1:PD-L1 interaction; however, although PD-1 and PD-L1 appear to play a role in chemotaxis, this is unlikely a reflection of iNKT-cell chemokine receptor expression changes.